New Institutional Theory: Implementasi Anggaran Berbasis Kinerja Menuju Organisasi Yang Kompetitif Dan Berorientasi Pasar - Astutiningrum Astutiningrum; Ali Djamhuri; Yeney Widya Prihatiningtias (Jurnal Reviu Akuntansi dan Keuangan, 2017)
The purpose of this study was to understand the organizational changes that occurred after theadoption of the performance-based budgeting. Organizational change was analyzed from theperspective of the NIT with a research focus on the process of implement performance-basedbudgeting in dr. Iskak Tulungagung Hospital. The research strategy is a case study with aqualitative approach. Results of research indicate the occurrence of coercive isomorphism, as aneffort to gain legitimacy, which is supported by mimetic ishomorphism, which attempts impersonation of another organization, although it is weak. The dominant symptom is normativeishomorphism, as indicated by the members of the organization normative belief that performance-based budgeting system is most appropriate for the characteristics of the hospital. Theimplementation of performance-based budgeting has encouraged the use of funds more effectively and efficiently, so that dr. Iskak Tulungagung likely to benefit in order to motivate organizations become morecompetitive and at the same time market-oriented.Ke ywords: Organizational Changes, Performance-Based Budgeting, Hybrid Organization, NewInstitutional Theory